Diabetes mellitus in relation to colorectal tumor molecular subtypes: A pooled analysis of more than 9000 cases. Issue 3 (22nd April 2022) - Harlid, Sophia; Van Guelpen, Bethany; Qu, Conghui; Gylling, Björn; Aglago, Elom K.; Amitay, Efrat L.; Brenner, Hermann; Buchanan, Daniel D.; Campbell, Peter T.; Cao, Yin; Chan, Andrew T.; Chang‐Claude, Jenny; et al.
Abstract: Diabetes is an established risk factor for colorectal cancer. However, colorectal cancer is a heterogeneous disease and it is not well understood whether diabetes is more strongly associated with some tumor molecular subtypes than others. A better understanding of the association between diabetes and colorectal cancer according to molecular subtypes could provide important insights into the biology of this association. We used data on lifestyle and clinical characteristics from the Colorectal Cancer Family Registry (CCFR) and the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO), including 9756 colorectal cancer cases (with tumor marker data) and 9985 controls, to evaluate associations between reported diabetes and risk of colorectal cancer according to molecular subtypes. Tumor markers included BRAF and KRAS mutations, microsatellite instability and CpG island methylator phenotype. In the multinomial logistic regression model, comparing colorectal cancer cases to cancer‐free controls, diabetes was positively associated with colorectal cancer regardless of subtype. The highest OR estimate was found for BRAF ‐mutated colorectal cancer, n = 1086 (ORfully adj : 1.67, 95% confidence intervals [CI]: 1.36‐2.05), with an attenuated association observed between diabetes and colorectal cancer without BRAF ‐mutations, n = 7959 (ORfully adj : 1.33, 95% CI: 1.19‐1.48). In the case only analysis, BRAF ‐mutation was differentially associated with diabetes ( P difference = .03). For the other markers, associations with diabetes were similar across tumor subtypes. In conclusion, our study confirms the established association between diabetes and colorectal cancer risk, and suggests that it particularly increases the risk of BRAF ‐mutated tumors. Abstract : What's new? Diabetes is a well‐known risk factor for colorectal cancer, but colorectal cancer varies widely among patients. To better understand the association between diabetes and particular molecular subtypes of colorectal cancer, these authors analyzed data from 9, 756 colorectal cancer cases and 9, 985 controls. They found that diabetes appears to increase the risk of tumors with BRAF mutations, which generally have poorer outcomes. The large pooled dataset allowed detection of even small variations among subtypes, but the study also was not able to account for some potentially relevant factors, such as metformin use.